2016
DOI: 10.3390/nu8120775
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Weight Cycling: Impact on Injury, Illness, and Inflammation in Collegiate Wrestlers

Abstract: This study explored the link between vitamin D status and frequency of skin infections, inflammation, and injury in college wrestlers during an academic year. Methods: Serum 25-hydroxyvitamin D (25(OH)D) (n = 19), plasma cytokine (TNF-α, IL-6, IL-10) (n = 18) concentrations, and body weight/composition were measured and injury/illness/skin infection data were collected in fall, winter, and spring. Results: In the fall, 74% of wrestlers had vitamin D concentrations <32 ng/mL which increased to 94% in winter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
1
18
1
Order By: Relevance
“…Heller et al [ 21 ] found that serum 25(OH)D concentrations were negatively associated with BMI and % body fat in 42 male and female athletes who participate in several kinds of sports. A similar result was also observed in collegiate male wrestlers, and the negative relationship between serum 25(OH)D concentrations and % body fat was observed regardless of seasonal changes [ 22 ]. In the present study, correlation analyses showed that serum 25(OH)D concentrations were not related to any of the body fat variables, including BMI, % body fat, WC, and SFA in collegiate football athletes, except there was a trend of a negative correlation between serum 25(OH)D and VFA ( r = −0.307, p = 0.083).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Heller et al [ 21 ] found that serum 25(OH)D concentrations were negatively associated with BMI and % body fat in 42 male and female athletes who participate in several kinds of sports. A similar result was also observed in collegiate male wrestlers, and the negative relationship between serum 25(OH)D concentrations and % body fat was observed regardless of seasonal changes [ 22 ]. In the present study, correlation analyses showed that serum 25(OH)D concentrations were not related to any of the body fat variables, including BMI, % body fat, WC, and SFA in collegiate football athletes, except there was a trend of a negative correlation between serum 25(OH)D and VFA ( r = −0.307, p = 0.083).…”
Section: Discussionsupporting
confidence: 73%
“…Heller et al [ 21 ] found that serum 25(OH)D concentrations were negatively associated with total body fat indicators, such as BMI and % body fat, even after controlling for sex in collegiate athletes. Additionally, Barcal et al [ 22 ] found a negative relationship between serum 25(OH)D concentrations and % body fat in collegiate male wrestlers, regardless of seasonal changes. Recently, in addition to body fat tissue, circulating 25(OH)D concentrations have been negatively associated with ectopic lipid content in adults in the general population [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few discussed whether their cut‐offs for vitamin D status were based upon a particular scientific body's recommendations (such as the IOM), or their own, to improve the presentation of their data. Insufficient 25(OH)D concentrations have also been identified within different young athletic populations, where prevalence rates (defined by the authors as <80 nmol/l) were reported to be 74% of a group of wrestlers (Barcal et al ), 37.7% of a group of ice hockey players (Fitzgerald et al ), 13% of a group of swimmers and divers (Lewis, Redzic & Thomas ) and 30.6% of a group of jockeys (Wilson et al ), which would suggest that there is a need to promote awareness of the importance of vitamin D for general health and physical performance (such as aerobic fitness and muscular strength) within young athletic population groups.…”
Section: What Is the Vitamin D Status Of University Athletes?mentioning
confidence: 99%
“…Studies conducted at different latitudes, including the US (Halliday et al ; Fitzgerald et al ; Villacis et al ; Barcal et al ; Jung et al ), Europe (Koundourakis et al ; Aydın et al ) and the UK (Owens et al ; Todd et al ), also indicate that university and recreational populations are at risk of a low vitamin D status (<50 nmol/l). It is important to note that the cut‐offs used within these university studies ranged from 25 to 80 nmol/l for 25(OH)D insufficiency and limited scientific justification was given for why they had chosen a particular cut‐off for vitamin D status.…”
Section: What Is the Vitamin D Status Of University Athletes?mentioning
confidence: 99%
“…Recently, vitamin D 3 supplementation has received wide attention in the athletic communities because vitamin D deficiency or insufficiency is a prevalent issue among athletes such as swimmers [ 17 ], football athletes [ 18 ], wrestlers [ 19 ], and taekwondo athletes [ 20 ]. Vitamin D deficiency has been associated with low physical performance level as well as high susceptibility to URTI.…”
Section: Introductionmentioning
confidence: 99%